5G Wireless Communication and Its Adverse Effects on the Human Body: Distinguishing Falsehoods from Reality - Bale, Ajay Sudhir; Soni, Sabhyata Uppal; Rajput, Dheeraj Singh; R., Hamsalekha; Saranya, S.; Joy, Salna; Chithra R., Baby; Savadatti, Mamta B. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
5G is the newest technology for wireless communication available. It allows gadgets like smartphones and Bluetooth-enabled gadgets to share information with one another. Electromagnetic radiation is the sort of energy that 5G uses to function. It's speedier and more efficient since it employs greater frequencies than other wireless connections. Electromagnetic fields (EMFs) are created when electromagnetic frequencies, such those generated by 5G, are introduced to a region. EMFs are thought to be harmful by some. Therefore, many are worried about the effects of 5G on their health. However, 5G has not yet been connected to any serious health concerns. There were various suggestions about the relationship among 5G and COVID'19, but neither of them was backed by evidence. There had been no real-world analogies, therefore it was reasonable to believe they were all hoaxes. With this article, we have made an effort to explore the various cases that justify these claims.